Social Assimilation Of Tionghua Muallaf (Converted Muslim) Residing In West Pontianak County - Baharuddin, Baharuddin (Universitas Tanjungpura)
This research aims at describing a social assimilation of Tionghua muallaf (converted Muslim) residing in West Pontianak County, Pontianak City of West Kalimantan. There are several important findings of this work with regards to the Tionghua muallaf including; Social Condition Group of Tionghoa Muallaf In West Pontianak District, Assimilate Process of Tionghoa Muallaf After Entering Islam, and Resistances Group of Tionghoa Muallaf. The social condition of the muallaf suggests that they convert to Islam due to several reasons including their new marital life, receiving hidayah (guidance) from Allah, having knowledge about Islam before converting to Islam, having seen the benefits and chances in their life such as satisfaction, peace, prosperity, patient, high respect to gifts from Allah and wanting to have a better life and clean heart in life.The convert process includes through religious clerics, the local offices of religious affair (Kantor Urusan Agama), extended parents and respected public figures; the assimilation process of the Tionghua muallaf shows that the Tionghua muallaf have not had better social relation with their Muslim neighbors, not been courageous enough to practice their Islam in public sphere, not done better assimilation within their new communities and not decided their direction of their new life with Islam; the discussion of constrain issues of the Tionghua muallaf indicate that they practice close relation within them, do not have jobs, do not have good motivations of life due to their lacks of hard work courage, they are low respect to their opportunities and self capabilities, selfish and less public care, good communication, less understanding of their new life, do not have enough time to study Islam due to the limitation of available teachers, practice Islam with instant hopes, think about economic benefits in all activities and are less involved in both formal and informal religious support institutions. Based on the above findings the work proposes some important recommendations including (1) it is important to encourage/develop a better relationship model; (2) it is also important to encourage/develop an Islamic and based-on-Quran-and-Hadist environment for the Tionghua muallaf; (3) if there is any problems and issues related to practicing Islam the muallaf should soon ask Islamic clerics and teachers; (4) it is important to give guidance and care to the muallaf having low courage to maximally practice their new religion; and (5) there should be a call to practice harmonic life within the Tionghua muallaf with better daily interaction, care and hospitality. Key words: assimilation, muallaf and Tionghua